Effect of moxibustion on knee joint stiffness characteristics in recreational athletes pre- and post-fatigue - Yufeng Zhang; Zirong Bai; Zhiye Zhang; Peng Yuan; Yilin Xu; Zun Wang; David Sutton; Jun Ren; Eamonn Delahunt; Dan Wang (Asia-Pacific Journal of Sports Medicine, Arthroscopy, Rehabilitation and Technology, 2023)
Objective: Joint stiffness results from the coupling of the nervous system and joint mechanics, and thus stiffness is a comprehensive representation of joint stability. It has been reported that moxibustion can alleviate general weakness and fatigue symptoms and subsequently may influence joint stiffness. This study investigated whether moxibustion could enhance knee joint stiffness in recreational athletes pre- and post-fatigue. Methods: Eighteen participants were randomized into intervention (5 males: 20.6 ± 1.5 yr; 4 females: 20.8 ± 1.5 yr) and control groups (5 males: 19.4 ± 0.9 yr; 4 females: 20.5 ± 0.6 yr). The intervention group received indirect moxibustion applied to acupoints ST36 (bilateral) and CV4 for 30 min every other day for 4 consecutive weeks. The control group maintained regular exercise without moxibustion. Peak torque (PT) of right knee extensor, relaxed and contracted muscle stiffness (MS) of vastus lateralis, and knee extensor musculoarticular stiffness (MAS) was assessed with an isokinetic dynamometer (IsoMed 2000), myometer, and free oscillation technique, respectively. Measurements were taken at three time points: pre-intervention, post-intervention/pre-fatigue, and post-fatigue. Results: MAS (P = 0.006) and PT (P = 0.007) in the intervention group increased more from pre-to post-intervention compared with the control group. Post-fatigue MAS (P = 0.016) and PT (P = 0.031) increased more in the intervention group than in the control group. Conclusion: Moxibustion enhanced PT and knee MAS, suggesting that this intervention could be used in injury prevention and benefit fatigue resistance in young recreational athletes.